GOVERNMENT RESPONSIBILITY FOR WORKERS WHO EXPERIENCE UNEMPLOYMENT DUE TO COVID -19 - Gempar Putra Firdaus; Risma Dewi Hermawan; Aris Prio Agus Santoso (DUTA BANGSA UNIVERSITY INDONESIA, 2021)
Right now the whole world, including Indonesia, is feeling uneasy because of the problem about Covid-19 which has caused losses in various sectors of life. The most visible losses are in public health, the economy and in other sectors. The most pronounced example is in the economic sector. Because many companies have been forced to reduce their workforce, so many people have lost their livelihoods. This article contains a discussion of the role of the government in dealing with unemployment in Indonesia during the Covid-19 pandemic. The purpose of writing this article is to find out how the steps have been and will be taken by the government to deal with the current unemployment problem. The approach method in this study uses a statutory approach (statute appoarch). This method examines the law based on legal norms and literature. The final result of this research is the government's efforts to deal with unemployment during the Covid-19 pandemic and the success rate or effectiveness of government policies on legal protection for Indonesian Workers during the pandemic. Based on the data analysis carried out, to deal with unemployment, the government issued several policies that could be used as solutions for workers to survive during the Covid-19 pandemic, several policies, namely: the pre-employment card policy which aims to eradicate poverty and reduce unemployment, Training Center Work,